Varietal performance of cabbage on the incidence of flea beetles (Phyllotreta spp.) - Islam, M. R.; Ali, M. R.; Ahmed, W. R.; Rahman, M. M.; Hira, H. (ENTOMOLOGIA HELLENICA, 2015)
A study was conducted at the Sher-e-Bangla Agricultural University, Bangladesh, during September 2007 to February 2008 to evaluate the varietal performance of cabbage on the incidence of flea beetles [Phyllotreta spp., (Coleoptera: Chrysomelidae)]. The experiment was laid out in a Randomized Complete Block Design comprising seven varieties viz. V1: BARI badhakopi-1/Provati, V2: BARI badhakopi-2/Agrodot, V3: Atlas-70, V4: Autumn queen, V5: Tropical queen, V6: T-776 and V7: Seisho YR. Among the different varieties of cabbage V5 (Tropical queen) performed as the best variety in terms of the lowest incidence of flea beetles (0.00 larvae/plant), lowest percent of leaves infestation (0.87 %) as well as plant infestation (2 %) caused by flea beetles. These findings will be valuable for the most appropriate management of flea beetles.